2014
DOI: 10.2298/hemind130124069j
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of 137Cs in the soil of Belgrade region (Serbia)

Abstract: Among radionuclides in the soil deposited after Chernobyl accident, 137Cs poses considerable environmental and radiological problems because of its relatively long half-life (30.17 y), its abundance in the fallout, high mobility and similarity to potassium as the major plant nutrient. In this study the samples of undisturbed surface soil (n=250) were taken from 70 regions in Belgrade, during 2006-2010. The specific activities of 137Cs were measured by gamma-ray spectrometry. Based on obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results of the research by Krstić et al [38] showed that Cs-137 binds to the surface layer of the soil, up to a depth of 10 cm, and that its concentrations decrease with depth. According to results obtained by Janković-Mandić et al [28], the specific activity of Cs-137 in the soil samples collected from different locations in Belgrade was in the range of 3 to 87 Bq kg −1 , with the mean value of 23 Bq kg −1 . The authors explained that the expressed variability in activity of Cs-137 was a result of topographical differences and inhomogeneous surface contamination of the soil after the Chernobyl accident.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The results of the research by Krstić et al [38] showed that Cs-137 binds to the surface layer of the soil, up to a depth of 10 cm, and that its concentrations decrease with depth. According to results obtained by Janković-Mandić et al [28], the specific activity of Cs-137 in the soil samples collected from different locations in Belgrade was in the range of 3 to 87 Bq kg −1 , with the mean value of 23 Bq kg −1 . The authors explained that the expressed variability in activity of Cs-137 was a result of topographical differences and inhomogeneous surface contamination of the soil after the Chernobyl accident.…”
Section: Resultsmentioning
confidence: 78%
“…Mihaljev et al [27] conducted a study of the concentration of radionuclides in samples collected from three locations of the Danube River, two ponds and one lake on Fruška Gora, in which six types of fish (catfish, perch, pike, carp, carp, and carp) were examined. In the research of Janković-Mandić et al [28], the presence of Cs-137 was determined in all samples of uncultivable land from the area of the city of Belgrade. Large variations in the specific activity of the radionuclide, as well as the dose derived from it, were determined, which were attributed to spatial differences in the physical-chemical and biological properties of the soil, the soil type, and the fauna.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Serbia, 137 Cs mainly originated from the Chernobyl accident while its much smaller portion derives from atmospheric nuclear weapons tests (Petrović et al 2013;Janković-Mandić et al 2014). After the Chernobyl accident, the spatial and vertical migration of the 137 Cs in soil has become the main goal of a number of studies in Serbia (Bikit et al 2005;Dugalic et al 2010;Grdović et al 2010;Dragović et al 2012a;Petrović et al 2013).…”
Section: Introductionmentioning
confidence: 99%